A polypropylene-degrading Psychrobacillus strain isolated from a landfill - Li, Yunhan; Zhao, Jindi; Wang, Panlin; Zhang, Zhidong; Zhang, Lihui (Journal of Environmental Engineering and Landscape Management, 2024)
Polypropylene (PP) is one of the most widely used plastics around the world. However, PP is recalcitrant to degradation under natural conditions, and its accumulation is increasingly threatening the environment. The stain LICME-ZWZR-10 was isolated from a landfill using PP as its sole carbon source. It was found to share 99.50% genetic similarity with Psychrobacillus sp. AK 1817. Upon incubation with Psychrobacillus sp. LICME-ZWZR-10, PP particles developed a rough surface with depressions and cracks, which were discerned through scanning electron microscopy (SEM). At a moderate temperature of 20 °C, this strain successfully degraded PP particles with an average diameter of 850 μm, leading to a 9±0.40% reduction in particle weight over a span of 30 days. Fourier transform infrared spectroscopy (FTIR) released the emergence of carbonyl and ether-based functional groups on PP. Furthermore, genomic analysis unveiled the presence of a laccase-encoding gene in Psychrobacillus sp. LICME-ZWZR-10, suggesting its potential involvement in the biodegradation of PP.